Ensuring public health in war and emergency situations for greater social resilience - Potočnik, Gregor (Teorija in praksa, 2025)
State and social resilience is a salient topic in current political and, thus, defence and military strategic decision-making. The increased armament capabilities of states is a consequence of the rise in state and social resilience. Among the general hysteria of increasing military firepower alone, one cannot avoid the feeling that many areas of social resilience, as key state infrastructure, are being ignored. A generally ignored part of critical infrastructure is the area of public health. In this article, a broad outline is provided of the EU and especially the Slovenian public health system, while an operational-tactical plan for public health in emergency or war situations is proposed.
Keywords: disaster medicine; extraordinary circumstances; izredne okoliščine; izredno stanje; Javna infrastruktura; javno zdravje; katastrofna medicina; public health; state of emergency; state of war; vojno stanje; Zdravstvo